28 GHz compact dipole antenna array integrated in fan-out eWLB package. Issue 10 (21st December 2022) - Aziz, Imran; Wu, Dapeng; Öjefors, Erik; Hanning, Johanna; Dancila, Dragos
Abstract: In this paper, we present a 28 GHz antenna array in package which covers the n257 and n258 frequency bands designated for 5G applications. The dipole antenna array is placed on one of the two re-distribution layers in the fan-out eWLB (embedded Wafer Level Ball Grid Array) package. For TX and RX, separate but identical antenna arrays are placed on each side of the die. The paper presents a novel horn-shaped heatsink which not only dissipates the heat, but also improves the radiation performance. The four-elements dipole array has the impedance bandwidth of almost 6 GHz (24–30 GHz) and shows a maximum realized gain of 9.5 dBi. Beam-steering in ± 35 deg is achieved in the azimuth plane (H-plane) by providing different phases to the dipoles through the chip. The measurements nicely agree with the simulation results.